EXPLORING READING LITERACY POLICIES AND PRACTICES: A CASE STUDY OF ONE REMOTE AREA OF KAZAKHSTAN - Sharipova, Kyrmyzy (Nazarbayev University Graduate School of Education, 2025)
This case-based study examines policies and practices related to reading literacy in one remote area of Kazakhstan. In recent years, Kazakhstan has actively implemented various initiatives to enhance schoolchildren’s reading literacy. Nationwide projects such as Reading School and Children’s Library, part of the broader Birtutas Tarbie national initiative, reflect these efforts. By drawing on existing literature, this study explored: (1) policies and practices currently employed to develop and implement reading literacy in remote schools in Kazakhstan; (2) stakeholder engagement in developing these policies and practices; and (3) key opportunities and challenges in promoting reading literacy in remote schools. The data collection involved three methods: (1) face-to-face semi-structured interviews, (2) observations, and (3) document analysis. Findings reveal that while existing policies and practices encourage stakeholder involvement—including teachers, learners, parents, and librarians—a lack of coherence and alignment undermines their effectiveness. Many stakeholders perceive these initiatives as performative, aimed at fostering a favorable impression rather than achieving substantial improvements. This performativity affects motivation and trust among stakeholders, leading to disengagement. Digital media emerged as both an opportunity and a challenge in the context of reading literacy development. Based on these findings, the study recommends the following measures: (1) formulating a clear, long-term strategic plan with specific, actionable goals tailored to local conditions, (2) actively incorporating stakeholder feedback to ensure policies and practices are relevant and practical, and (3) addressing the influence of digital media on learners by integrating technology in meaningful ways to support reading initiatives.
Keywords: Reading literacy; remote schools; education policy; Type of access: Open